2022
DOI: 10.1002/app.52149
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation on particle‐reinforced rigid/flexible composites via fused deposition modeling3Dprinting

Abstract: The diversity of filament consumables is the basis for developing of fused deposition modeling (FDM) 3D printing industry. At the same time, the blending of matrix materials and the addition of reinforcing materials are the manufacturing difficulties of this composite 3D printing consumable. In this article, poly(lactic acid) (PLA)/thermoplastic polyurethane (TPU)/organic montmorillonite (OMMT) composites were manufactured to systematically study the characteristics and laws of these composites. Both the rigid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
(46 reference statements)
0
8
0
Order By: Relevance
“…This is due to the blend structure of PCL and CTFA (there is no copolymerization or crosslinking between components), and the discontinuity of the poly(CTFA) short‐chain. Therefore, the stress and strain of this two‐phase material under stress are significantly lower than the linear theoretical value of the component material according to rule of mixture 22,27,28 . Because the flexibility of PCL is much larger than that of CTFA polymer, a small amount of PCL is also considered as foaming agent in CTFA samples to improve the toughness of CTFA to avoid damage.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…This is due to the blend structure of PCL and CTFA (there is no copolymerization or crosslinking between components), and the discontinuity of the poly(CTFA) short‐chain. Therefore, the stress and strain of this two‐phase material under stress are significantly lower than the linear theoretical value of the component material according to rule of mixture 22,27,28 . Because the flexibility of PCL is much larger than that of CTFA polymer, a small amount of PCL is also considered as foaming agent in CTFA samples to improve the toughness of CTFA to avoid damage.…”
Section: Resultsmentioning
confidence: 96%
“…Therefore, the stress and strain of this two-phase material under stress are significantly lower than the linear theoretical value of the component material according to rule of mixture. 22,27,28 Because the flexibility of PCL is much larger than that of CTFA polymer, a small amount of PCL is also considered as foaming agent in CTFA samples to improve the toughness of CTFA to avoid damage. However, the distribution of PCL in the polymer is uneven, so it is not recommended to continuously add it.…”
Section: Tensile Stress-strain Curvesmentioning
confidence: 99%
“…The AM technologies for polymers include fused deposition modeling (FDM), stereo lithography appearance (SLA), and ink direct writing (DIW). , Especially, FDM is characterized by low cost, multiple varieties, and flexible structural design. PLA and TPU are currently the most commonly used FDM-3D printing consumables. , Compared to liquid consumables such as SLA and DIW, the polar molecular structure and high molecular weight of these FDM consumables not only ensure the formability of 3D printed products but also lead to excellent mechanical performance.…”
Section: Introductionmentioning
confidence: 99%
“…8−10 PLA and TPU are currently the most commonly used FDM-3D printing consumables. 11,12 Compared to liquid consumables such as SLA and DIW, the polar molecular structure and high molecular weight of these FDM consumables not only ensure the formability of 3D printed products but also lead to excellent mechanical performance.…”
Section: Introductionmentioning
confidence: 99%
“…Nieddu et al [ 19 ] noticed that PLA nanocomposites showed an improvement in the modulus as a function of the type and the content of clay compared with the pure polymer. The addition of organomodified montmorillonite (OMMT) with 5 wt.% enhanced the mechanical and thermal behavior of polymers as well as the processibility of PLA-based and TPU-based composites [ 20 ]. Moreover, PLA-based blends with a small loading of nanoclay (1 to 5 wt.%) and Joncryl (0.3 phr) are extremely interesting in the case of 3D printing technologies [ 21 ].…”
Section: Introductionmentioning
confidence: 99%